0
$\begingroup$

I am currently trying to solve:

$$\left(\frac{d^{61}}{dt^{61}}\right)(e^{-t+1} cos⁡(t))$$

So far I've converted cos(t) into Re($e^{it}$) and thus got Re($e^{(-1+i)t+1}$). This is where I've gotten a bit stuck. I tried separating it out into Re($e^{(-1+i)t}e^{1}$) and then using the product rule to solve that, but I'm not sure whether that's valid, and if it is, where to go from there in solving the problem.

$\endgroup$
4
  • 1
    $\begingroup$ Welcome to Math.SE! Did you intend to write $=$ there? $\endgroup$ Sep 6, 2020 at 5:35
  • $\begingroup$ @KevinLópezAquino Nope, sorry! I've gotten rid of it now. $\endgroup$ Sep 6, 2020 at 5:51
  • $\begingroup$ You can do that, or just write 2cosx = e^ix + e^-ix $\endgroup$ Sep 6, 2020 at 5:55
  • $\begingroup$ The $61$-st derivative of $e^{(-1+i)t}$ is $(-1+i)^{61}e^{(-1+i)t}$. $\endgroup$ Sep 6, 2020 at 6:15

1 Answer 1

3
$\begingroup$

We can continue on the track that you have. Using the fact that

$$\frac{d^n}{dt^n}e^{\lambda t} = \lambda^n e^{\lambda t}$$

we get

$$e\frac{d^{61}}{dt^{61}}e^{(-1+i)t} = e\cdot(-1+i)^{61}e^{(-1+i)t}$$

Convert the complex number to polar form to compute the power

$$-1+i = \sqrt{2}e^{i\frac{3\pi}{4}} \implies (-1+i)^{61} = 2^{\frac{61}{2}}e^{i\frac{183\pi}{4}} = -2^{30}\cdot\sqrt{2} e^{i\frac{3\pi}{4}}=2^{30}(1-i)$$

which means we can rewrite the complex derivative as

$$e^{-t+1}\cdot 2^{30}\cdot(1-i)\cdot(\cos t + i\sin t)$$ Taking the real part gives us the final answer

$$\frac{d^{61}}{dt^{61}}e^{-t+1}\cos t = 2^{30}e^{-t+1}(\cos t+\sin t)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.